Social Commerce Investigation: The Role of Satisfaction and Loyalty on Repurchase Intention - Gemilang, Ahcmad Rivai Sinar; Marsasi, Endy Gunanto (Politeknik Negeri Padang, 2023)
This study aims to find evidence of the effect of satisfaction and loyalty on repurchase intentions in social commerce through social exchange theory. This research focuses on five variables: reputation, information quality, satisfaction, loyalty, and repurchase intention. This research is motivated by satisfaction, which is not optimal in shaping repurchase intentions. Loyalty is an aspect of novelty in this research. The research method used is a quantitative approach. Data collection techniques support this research through online questionnaires. The data used in this study are primary as many as 219 respondents. Data processing analysis uses the Structural Equation Modeling (SEM) method and is supported by SPSS 25 and IBM AMOS 22 software. This study's results indicate that satisfaction significantly affects loyalty and repurchase intentions in social commerce. The results also found that loyalty has no significant effect on repurchase intentions. Satisfaction is an important factor for a user to have the intention to repurchase in the same place. A good reputation and quality information social commerce provides influence this.